Advancing Cancer Care: A Critical Review of MRI Imaging in Pretherapeutic Malignancy Assessment - AlHarbi, Nawaf Mesfer; AlHarbi, Fayez Hamdan; Al-Shalali, Abdul Majeed Salem; Alheary , Waleed Eissa; Althbyani , Bndar Mohamed; Alaeinbawi, Marwan Hamed; Alrehaili , Hamzah Atiah S; AL-Khateeb, Mohammed Hamed; Alaufi, Ahmad Barakah; Al Khalawi , Mohammed Saad (Journal of Ecohumanism, 2024)
Magnetic Resonance Imaging (MRI) has become an indispensable tool in the pretherapeutic assessment of malignancies, offering unparalleled soft tissue contrast, advanced functional imaging capabilities, and the ability to provide non-invasive, radiation-free evaluations. This critical review explores the role of MRI in accurately diagnosing, staging, and guiding treatment strategies for various cancers, including breast, prostate, liver, and brain malignancies. Advanced techniques such as diffusion-weighted imaging (DWI), dynamic contrast-enhanced MRI (DCE-MRI), and the integration of artificial intelligence are discussed for their potential to enhance diagnostic precision and treatment planning. Despite its significant advantages, including superior detection of occult lesions, MRI faces challenges such as high costs, accessibility, and occasional diagnostic pitfalls. This review emphasizes MRI's transformative impact on cancer management, discusses its limitations, and highlights ongoing innovations that aim to improve its clinical utility and accessibility. The findings underscore MRI’s pivotal role in enhancing personalized medicine and optimizing therapeutic outcomes for cancer patients.